Postpartum depression and associated factors among mothers who gave birth in the last twelve months in Ankesha district, Awi zone, North West Ethiopia - Solomon Shitu; Biftu Geda; Merga Dheresa (BMC, 2019)
Abstract Background Postpartum depression is the most common complication of childbearing age women and is a considerable public health problem. The transition into motherhood is a difficult period that involves significant changes in the psychological, social and physiological aspects, and has increased vulnerability for the development of mental illness. More than 1 in 10 pregnant women and 1 in 20 postnatal women in Ethiopia suffer from undetected depression. Methods Community based cross sectional study was conducted among 596 postpartum mothers in Ankesha District, North West Ethiopia, from February 01 to March 2, 2018. One stage cluster sampling technique was employed to get the study participants. The objective was to assess the prevalence and associated factors of postpartum depression among mothers who gave birth in the last Twelve months in Ankesha District, Awi Zone, North West Ethiopia, 2018. The interviewer-administered questionnaire was used to collect data and Eden Burg Postpartum Depression Scale was used to assess postpartum depression with cutoff point ≥8. The data were entered into Epi data version 3.1 and exported to SPSS version 24 for analysis. All variables with P < 0.25 in the bivariate analysis were included in the final model and statistical significance was declared at P < 0.05. Result In this study, a total of 596 study participants were involved making a response rate of 97.4%, the prevalence of postpartum depression was 23.7% with 95%CI: 20.3-27.2. From the participant mothers who are divorced/widowed/unmarried (AOR = 3.45 95%CI: 1.35-8.82), unwanted pregnancy (AOR = 1.95 95%CI: 1.14-3.33), unpreferred infant sex (AOR = 1.79 95%CI: 1.13-2.86), infant illness (AOR = 2.08 95%CI: 1.30-3.34) and low social support (AOR = 3.16 95% CI: 1.55-6.43) was independent predictors of postpartum depression. Conclusion Almost a quarter (23.7%) of women suffers from postpartum depression. Marital status, unwanted pregnancy, unwanted infant sex, infant illness, and low social support were independent predictors of postpartum depression. Therefore, integration of mental illness with maternal and child health care is important, information communication education and behavioral change communications on postpartum depression are better been given attention.